Social problems a human rights perspective - Bonds, Eric 1976- (Framing 21st century social issues, 2021)
Social Problems: A Human Rights Perspective 2nd Ed. evaluates U.S. society through an international human rights framework. The book provides a critical discussion about what rights mean and a sociological exploration of power and inequality to explain why human rights are so often violated or left unfilled in the United States. In each chapter, the book offers numerous policy alternatives that could provide a pathway toward the increased fulfillment of rights, while also stressing the important role that nonviolent social movements have had, and must have in the future, in achieving greater justice, dignity, wellbeing, and environmental protection in our society. This edition includes several new chapters on topics of major interest to students, including: The human right to health. Climate change and human rights. Immigration and human rights violations in U.S. society. A new discussion of the #BlackLivesMatter movement Social Problems gives social science students a new way to understand pressing social issues that exist in their own communities"--